UPLC-MS/MS method for Icariin and metabolites in whole blood of C57 mice: development, validation, and pharmacokinetics study - Liu, Wei; Li, Xiuyun; Li, Na; Mi, Ze; Li, Na; Che, Jinjing (Frontiers in Pharmacology, 2023)
Icariin, a Chinese medicinal herb with significant effects on Alzheimer's disease, lacks pharmacokinetic data in mice. To address this, a UPLC-MS/MS method was developed and validated for quantifying Icariin and its metabolites, Icariside I and Icariside II, in the whole blood of mice. The method processed micro-whole blood from serial collections of the same C57 mouse, with well-fitted linearity (0.25-800 ng·mL-1) and intra- and inter-day precision and accuracy within 15%. Short-time and autosampler stability were verified, with acceptable extraction recoveries and matrix effects over 74.55%. After intravenous administration (15 mg·kg-1) of Icariin in C57 mice, Icariside I and Icariside II were detected within 2 minutes. However, after the intragastric administration (30, 90, and 150 mg·kg-1) of Icariin in C57 mice, Icariin and Icariside I were not detected, and Icariin was rapidly converted into Icariside II. Furthermore, the Cmax and AUC0-t of three doses (30, 90, and 150 mg·kg-1) of Icariside II increased as the dose increased. In conclusion, this method improves the traditional method of collecting only one blood sample from each mouse, detecting Icariin and its metabolites in the whole blood of mice, especially for serial collection of micro-whole blood.